The Point Cloud Visualisation For Rotary Optical Rangefinders - Chmelař, Pavel; Beran, Ladislav; Rejfek, Luboš; Chmelařová, Natalija (IEEE, 2017)
This paper describes the point cloud visualization for rotary optical rangefinders. Measured distance data with image information from captured frames give a possibility to create a colored point cloud. The distance is measured by the vertical laser line and to select a color value directly from an actual measured frame is not possible. For this reason, the previous measurement frame is used. The individual frames shifting is estimated by the temple matching algorithm. The purpose of the paper is to show how easily it is possible to combine measurement data with image information in case of a color point cloud construction. The paper includes several examples of different point clouds to verify the algorithm's ability.
The Point Cloud Visualisation For Rotary Optical Rangefinders
Keywords: point cloud; template matching; rotary optical rangefinder; laser measurement; point cloud library; point cloud; template matching; rotary optical rangefinder; laser measurement; point cloud library